Pengaruh variasi aliran udara terhadap optimasi daya panel surya - Pido, R.; Rahmat, B.H.; Wawan, R.; Rianto, D.R. (Universitas Mataram, 2023)
Solar panels are one of the most popular renewable energy technologies in this modern era. To optimize the performance of solar panels, many studies have been conducted to understand and improve the factors that affect the power generated by solar panels. In this experiment, the aim is to analyze the temperature setting for cooling solar panels using variations in air velocity to increase the performance of solar panels. In this study, solar panels were tested with variations in fluid flow velocity of 6.0 m/s, 5.5 m/s, and 4.4 m/s with an inclination angle of 15˚ solar panels facing north. with 60-minute intervals. The air blower is combined with an anemometer to provide variable air velocity for panel cooling. From the results of solar panel testing the maximum power generated at a wind speed of 4.4 m/s is 47.40 W, the power generated at a wind speed of 5.5 m/s is 47.55 W, and the power generated at a wind speed of 6 .0 m/s the maximum power generated is 48.65 watts. While the maximum efficiency produced at a wind speed of 4.4 m/s is 4.23%, and the minimum efficiency produced is 1.87%, the average efficiency is 26.56%. at a wind speed of 5.5 m/s, the maximum efficiency produced is 44.6%, the minimum efficiency is 1.95%, and the average efficiency is 27.86%. at a wind speed of 6.0 m/s, the maximum efficiency produced is 4.79%, the minimum efficiency is 2.07%, and the average efficiency is 29.29%.